The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008 23rd IEEE/ACM International Conference on Automated Software Engineering 2008
DOI: 10.1109/ase.2008.69
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics for Scalable Dynamic Test Generation

Abstract: Recently there has been great success in using symbolic execution to automatically generate test inputs for small software systems. A primary challenge in scaling such approaches to larger programs is the combinatorial explosion of the path space. It is likely that sophisticated strategies for searching this path space are needed to generate inputs that effectively test large programs (by, e.g., achieving significant branch coverage). We present several such heuristic search strategies, including a novel strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
274
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(276 citation statements)
references
References 24 publications
(28 reference statements)
1
274
0
1
Order By: Relevance
“…Despite the overhead in memory and time consumption related to caching (to store, lookup, and combine solutions), it has been observed that this optimization is beneficial. Popular symbolic execution tools, such as CREST [15], KLEE [16], PEX [32] and SPF [26], use similar features.…”
Section: Incremental Constraint Solving Approachesmentioning
confidence: 99%
“…Despite the overhead in memory and time consumption related to caching (to store, lookup, and combine solutions), it has been observed that this optimization is beneficial. Popular symbolic execution tools, such as CREST [15], KLEE [16], PEX [32] and SPF [26], use similar features.…”
Section: Incremental Constraint Solving Approachesmentioning
confidence: 99%
“…The Pex tool is not open-source but provides an extension interface. To the best of our knowledge, available open-source constraint-based testing tools are KLEE [14] (used as a core component of the S2E platform [63]) and CREST [64] (for C code) as well as Symbolic Path Finder [17] (for Java byte-code).…”
Section: Future Workmentioning
confidence: 99%
“…Symbolic [9,10,13], and the related concolic [8,17], execution are techniques for systematically exploring the code paths of a given system. The approaches in this space [9,8] use a constraint solver to force code executions to go down a particular branch.…”
Section: Related Workmentioning
confidence: 99%
“…The approaches in this space [9,8] use a constraint solver to force code executions to go down a particular branch. As such, these approaches typically do not require a testing harness when finding bugs in single machine code.…”
Section: Related Workmentioning
confidence: 99%